An Exploratory Study on Attention Deficits in Healthcare Professionals Experiencing Non-Clinical Burnout - Wejdan Safar Sahab; Salma Ali Alasmri; Hanan Mohammed Assiri; Hussam Ibrahim Qumayi; Ahmed Khalaf Alanzi; Khaled Alaa Mohammed Assiri; Ashwaq Bandar Halal Almutairi; Ebtesam Rashed Alhobeshi; Roqaiah Mosad Alwafi; Mohammed Dhaifallah Burayqi Alshammari; Sharifa Ali Galib Alshargi (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Burnout, a consequence of chronic workplace stress, is associated with physical, emotional, and cognitive impairments. Healthcare workers (HCWs), particularly during the Pandemics , faced significant stressors, making them a relevant group for studying non-clinical burnout (NCB). This study explored whether NCB impacts attention subdomains in HCWs, a cognitive domain critical for professional tasks and overall functioning. Methods: The study recruited HCWs aged 25–45, excluding individuals with confounding medical or neurological conditions, substance use, or prior COVID-19 infection. Participants were classified into NCB and control groups using the Maslach Burnout Inventory (MBI). Attention performance was assessed using the Continuous Visual Attention Test (CVAT), measuring reaction time (RT), variability in RT (VRT), omission errors (OE), and commission errors (CE). Multivariate and univariate analyses were conducted to identify group differences and correlations between burnout dimensions and attention deficits. Results: Among 154 participants, 26 met inclusion criteria (13 NCB and 13 controls). Significant group differences in CE were observed, with NCB participants demonstrating more inhibition errors (F(4, 21) = 12.90, p = 0.001, η² = 0.35). VRT analysis indicated a trend toward higher variability in the NCB group when controlling for RT. Correlations revealed significant associations between CE and burnout dimensions, including exhaustion (R = 0.545, p = 0.004) and cynicism (R = 0.563, p = 0.003), and an inverse relationship with personal efficacy (R = −0.522, p = 0.006). Conclusion: HCWs experiencing NCB exhibit deficits in executive attention, particularly in sustained attention and impulsivity. Incorporating brief computerized attention assessments, such as the CVAT, alongside self-reported burnout measures, may help identify individuals at risk for cognitive impairments. These findings underscore the importance of addressing burnout to mitigate workplace errors and inform policy interventions in high-stress occupations.